Prevalence of dog intestinal parasites and risk perception of zoonotic infection by dog owners in São Paulo State, Brazil - Katagiri, S. [UNESP]; Oliveira-Sequeira, T. C. G. [UNESP] (Blackwell Publishing, 2008)
Coprological examination was used to estimate the prevalence of gastrointestinal parasites in stray and domiciled dogs from Botucatu, São Paulo State, Brazil. Risk factors for dog infection were assessed in relation to demographic, husbandry and management data. The dog owners completed a questionnaire survey on some aspects of dog parasitism such as parasite species, mechanisms of infection, awareness of zoonotic diseases and history of anthelmintic usage. Parasites were found in the faeces of 138 dogs, with an overall prevalence of 54.3%. Dogs harbouring one parasite were more common (31.4%) than those harbouring two (18.5%), three (3.2%) or four (1.2%). The following parasites and their respective frequencies were detected: Ancylostoma (37.8%), Giardia (16.9%), Toxocara canis (8.7%), Trichuris vulpis (7.1%), Dipylidium caninum (2.4%), Isospora (3.5%), Cryptosporidium (3.1%) and Sarcocystis (2.7%). Stray dogs were found more likely to be poliparasitized (P < 0.01) and presented higher prevalence of Ancylostoma, T. canis and Giardia (P < 0.01) than domiciled ones. Toxocara canis was detected more frequently in dogs with < 6 months of age (P < 0.05) and no effect of sex or breed could be observed (P > 0.05). Except for Ancylostoma, that showed a significantly higher prevalence in dogs living in a multi-dog household (P < 0.01), parasite prevalences were similar in single- and multi-dog household. The answers of dog owners to the questionnaire showed that the majority does not know the species of dog intestinal parasites, the mechanisms of transmission, the risk factors for zoonotic infections, and specific prophylactic measures. The predominance of zoonotic species in dogs in the studied region, associated with the elevated degree of misinformation of the owners, indicates that the risk of zoonotic infection by canine intestinal parasite may be high, even in one of the most developed regions of Brazil.
Keywords: prevalence; intestinal parasites; dog; zoonoses; protozoa; helminths